Marketing de relacionamento como estratégia de fidelização e retenção de clientes: estudo de caso na empresa AutoForce - Dantas, Kamila Pereira Buriti (2021)
The development of technology over the years has brought about a series of transformations in global commerce, resulting in a more competitive scenario amongst companies, as customers grow more and more demanding about what they consume. Maintaining a long-lasting relationship with the customer, seeking to meet and satisfy their needs and generating a consequent recurrence of purchases, has become essential for any company seeking to differentiate itself from its competitors. Thus, the focus of marketing is no longer just winning new customers, to a new relational focus aimed at maintaining and retaining existing customers, giving rise to relationship marketing. In this way, relationship marketing has become essential for the survival of companies in the modern world. Therefore, this work addressed the reality of a company in the technology segment for the automotive sector, AutoForce, located in the city of Natal/RN, aiming to analyze how Relationship Marketing strategies can contribute to loyalty and retention of the company's customers. For this, an exploratory research was carried out, of the case study type, with an intentional non-probabilistic sampling, carried out through the application of semi-structured interviews with the Director of the Customer Success Team in the company and 6 Martech dealership customers. The results showed that even with a good relationship between the company and its customers, there are some points of this interaction that are not noticed by them and need improvement, so that a lasting relationship can be created between them. In addition, in general, the company demonstrates a strong focus on the online relationship with its audience, especially related to content marketing and social networks. AutoForce also showed good satisfaction numbers from its customers, resulting in a 9.3 NPS score.